2023
DOI: 10.21831/socia.v19i2.60152
|View full text |Cite
|
Sign up to set email alerts
|

Revitalisasi Pendidikan Kewarganegaraan Abad 21: Analisis Keterampilan Abad 21

Abstract: Revitalisasi Pendidikan Kewarganegaraan Abad 21 menjadi isu penting dalam menghadapi tantangan abad 21 yang semakin kompleks dan dinamis. Ketrampilan abad 21 menjadi fokus utama dalam upaya meningkatkan kualitas pendidikan kewarganegaraan, yang bertujuan untuk menghasilkan generasi yang siap menghadapi tantangan global dan menjadi warga negara yang aktif dan berkontribusi pada masyarakat. Penelitian kualitatif ini bertujuan untuk menganalisis data ketrampilan abad 21 yang terkait dengan pendidikan kewarganegar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…Indonesia citizenship education has a position and function as a valuable education, morals or character, and distinctive Indonesian citizenship which is very coherent, integrated with a commitment to develop a dignified national character and civilization and the realization of a democratic and responsible as stated in the article 3 of law on the National Education System (No. 20/2003) [11]. Therefore, it can be concluded that citizenship education in Indonesia is an integrated scientific study that examines citizens with all their activities to shape them into smart, skilled, loyal, and act by following under the mandate of Pancasila and the 1945 Constitution of the Republic of Indonesia.…”
Section: Civic Education In the Indonesian Contextmentioning
confidence: 99%
“…Indonesia citizenship education has a position and function as a valuable education, morals or character, and distinctive Indonesian citizenship which is very coherent, integrated with a commitment to develop a dignified national character and civilization and the realization of a democratic and responsible as stated in the article 3 of law on the National Education System (No. 20/2003) [11]. Therefore, it can be concluded that citizenship education in Indonesia is an integrated scientific study that examines citizens with all their activities to shape them into smart, skilled, loyal, and act by following under the mandate of Pancasila and the 1945 Constitution of the Republic of Indonesia.…”
Section: Civic Education In the Indonesian Contextmentioning
confidence: 99%
“…Abad 21 memberikan berbagai tantangan pada masyarakat (Suyato, Hidayah, Arpannudin, & Septiningrum, 2022). Pembelajaran resolusi konflik dalam PKn memberikan kesempatan bagi peserta didik untuk berlatih dalam mengelola konflik secara konstruktif.…”
Section: Resolusi Konflik Dalam Pembelajaran Pknunclassified
“…The advent of technology has revolutionized our modes of interaction, employment, and learning, granting unrestricted entry to knowledge via the internet, and facilitating global connections among individuals residing in disparate regions (Salsabila & Nawawi, 2023). As per the findings of Suyato et al (2023), globalization leads to transformations in the economic, cultural, and political systems, broadening the extent of connections between nations and cultures. This phenomenon presents novel problems and prospects that necessitate an educational methodology that is adaptable to evolving circumstances.…”
Section: Introductionmentioning
confidence: 99%